DIRECTIONS OF EFFECTIVE APPLICATION OF FOREIGN MANAGEMENT EXPERIENCE IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Conference Zone, 2022)
The goal of introducing modern mechanisms of pre-school education management, improving the education and training process, filling pre-school educational institutions with highly qualified specialists, and improving their infrastructure and material and technical equipment has become one of the priority directions. In the article, it will be discussed about the directions of effective application of foreign management experience in preschool educational organizations.